Structural evidence in Plectroniella armata (Rubiaceae) for possible material exchange between domatia and mites. - Patricia M Tilney (Public Library of Science (PLoS), 2012)
Domatia are small structures on the lower surface of a leaf, usually taking the form of cavities, pouches, domes with an opening, or hairs (or a combination of these), and located in the axils between the main veins. They are found in many dicotyledons including certain members of the Rubiaceae. As part of an ongoing study of selected southern African members of the tribe Vanguerieae of this family, their structure in transverse section was investigated. In some taxa, such as Plectroniella armata, light microscopic (LM) observations revealed large numbers of stomata in the domatia as well as a number of channel-like structures extending across the cuticle toward the cavity of the domatia. The cuticle of the epidermis lining the domatia also appeared thicker than in other parts of the leaves. The epidermis in P. armata was also examined using transmission electron microscopy (TEM). Domatia have been shown to house mainly mites, many of which are predatory or fungivorous, in a symbiotic (mutualistic) relationship with the plant. To date, much research has focussed on the role of domatia in providing shelter for various organisms, their eggs and their young. However, the TEM study revealed the apparent "channels" and thick cuticle seen under LM to be electron dense non-cellulosic branching fibrils within pronounced, often closely spaced cuticular folds. The functional significance of these fibrils and folds requires further investigation. Folding of cell walls and membranes at ultrastructural level is usually functionally associated with an increased surface area to facilitate active exchange of compounds/metabolites. This may indicate that translocation of substances and/or other forms of communication is possible between the domatium and its inhabitants. This therefore suggests a far more active role for the leaf in the symbiotic relationship than was previously thought. More work is required to test such a possibility.